2021
DOI: 10.1111/acel.13477
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic cervical thymi and no thymic involution until midlife in naked mole rats

Abstract: Immunosenescence is a hallmark of aging and manifests as increased susceptibility to infection, autoimmunity, and cancer in the elderly. One component of immunosenescence is thymic involution, age‐associated shrinkage of the thymus, observed in all vertebrates studied to date. The naked mole rat (Heterocephalus glaber) has become an attractive animal model in aging research due to its extreme longevity and resistance to disease. Here, we show that naked mole rats display no thymic involution up to 11 years of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…The low HSPC IFN signaling together with largely diminished cytotoxic CD8-TCs may explain the insufficient anti-viral response of NMRs. We also showed that total thymic cellularity was markedly lower in NMRs compared to mice (Emmrich et al, 2021). NMRs may not have evolved to deal with viral challenges because subterranean lifestyle with limited contact outside the native colony limits viral spread.…”
Section: Discussionmentioning
confidence: 81%
“…The low HSPC IFN signaling together with largely diminished cytotoxic CD8-TCs may explain the insufficient anti-viral response of NMRs. We also showed that total thymic cellularity was markedly lower in NMRs compared to mice (Emmrich et al, 2021). NMRs may not have evolved to deal with viral challenges because subterranean lifestyle with limited contact outside the native colony limits viral spread.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, the extremely long-lived subterranean rodent – the naked mole rat – has recently been shown to have not just one mediastinal thymus (as is typical for other mammals including humans), but also a few cervical thymi which apparently ascertain constant provision of new naïve T cells, prevent thymic involution until midlife of the mole rats, and in consequence, produce an extreme resistance of these animals to infections and cancers and increase their longevity [33] . Not surprisingly, this discovery yielded support to the search for ways of rejuvenation of our own thymuses as a way of prolonging healthy life.…”
Section: Immune System Aging – Basicsmentioning
confidence: 99%
“…More recently, NMR aged 3 and 11 years were used as compared to mice aged 3 and 12 months. They discovered that NMR owned an additional pair of cervical thymi and that they had no thymic involution up to 11 years of age, suggesting that they displayed a delayed immunosenescence [ 53 ]. Thus, we hypothesize that the maintenance of cellular compartments in the older NMR, especially the stem cell pool through high Igfbp3 expression, coupled with an increase skin immunity, could explain their skin slower rate of aging.…”
Section: Discussionmentioning
confidence: 99%